Synthesis of S-doped mesoporous carbon and its use in advanced supercapacitors and sodium-ion batteries - Zha-Xi Wan-Me; Hai-Tao Zhang; Yang Zhao; Hui-Zhan Wen; Xue-Ying Wan; Yu-Long Xie (Carbon Trends)
Rational design of mesoporous carbon materials with controllable pore structures and higher specific surface areas has always been a daunting challenge in advanced energy materials. Here, we propose a simple hydrothermal synthesis strategy for the preparation of sulfur-doped mesoporous carbon (SMC), which exhibits hierarchical porosity and a significantly increased specific surface area (650.22 m2 g-1). This structure is constructed through the molecular assembly of phenolic resin precursors with bifunctional sodium sulfate (simultaneously achieving sulfur doping and pore modulation), mediated by Pluronic F127 triblock copolymer as a mesostructure directing agent. System characterization indicates that the optimized SMC-0.1 material possesses excellent electrochemical properties: (1) as a supercapacitor electrode, it provides an outstanding specific capacitance of 188.9 F g-1 at 0.5 A g-1; (2) the fabricated symmetrical device (SMC-0.1//SMC-0.1) achieves an energy density of 5.12 Wh kg-1 at a power density of 150.07 W kg-1 in a 6 M KOH electrolyte; (3) when used as a sodium-ion battery anode, SMC-0.1 exhibits excellent rate capability and improved Na+ diffusion kinetics. This study proposes a general heteroatom doping method to design multifunctional carbon structures with broad applicability in advanced energy systems.